2011
DOI: 10.1111/j.1469-7610.2010.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxious attachment style and salivary cortisol dysregulation in healthy female children and adolescents

Abstract: These findings indicate that the same pattern of cortisol dysregulation associated with disorder in adulthood manifests as a function of anxious (but not avoidant) insecure attachment style in females during healthy childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 47 publications
9
33
1
2
Order By: Relevance
“…In this study, the relationship between a smaller CAR and fear of rejection was hypothesized and in 20 line with previous studies (Oskis et al, 2011;Quirin et al, 2008;Tops et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this study, the relationship between a smaller CAR and fear of rejection was hypothesized and in 20 line with previous studies (Oskis et al, 2011;Quirin et al, 2008;Tops et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
“…We tested two main hypotheses. First, in line with previous studies of adults and suggesting links between dysregulated diurnal cortisol profiles and insecure-anxious attachment (Kidd, Hamer, & Steptoe, 2013;Oskis et al, 2011;Quirin et al, 2008), we expected specific dimensions of attachment anxiety, including fear of rejection and separation/abandonment, would predict a flatter awakening response of cortisol. Second, in line with evolutionary-developmental theories of biological stress regulation, we expected less attachment behavior/support seeking towards the primary caregiver, manifested by less confiding (presumably reflecting greater adolescent autonomy), would predict higher levels of basal DHEA.…”
Section: The Current Studysupporting
confidence: 65%
See 1 more Smart Citation
“…Some studies have demonstrated the CAR to be associated with vulnerability to future disorder in healthy participants (e.g. Adam et al, 2014;Oskis et al, 2011). Concurrent well-being rather than measures of future vulnerability were the focus of this study, which may explain the failure to find associations.…”
Section: Discussioncontrasting
confidence: 39%
“…5,8,9 The findings in the insecure-avoidant and insecure-resistant attachment groups are inconsistent. In some studies, both insecure groups were found to have elevated cortisol levels, 8 others found increased cortisol levels only for insecure-resistant children.…”
Section: Introductionmentioning
confidence: 85%